CLINICAL AND PATHOGENETICAL PERCULARITIES OF ANTIHOMOTOXIC PREPARATIONS APPLICATION IN PATIENTS WITH ACUTE SALPINGOOPHORITIS - Grischenko, O.V.; Lakhno, I.V.; Tkachov, A.E.; Dudko, V.L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
It was performed the investigation of efficacy of patients with acute salpingoophoritis complex treatment with antihomotoxic preparations application. It was shown the restitution of vaginal microbial bіotop, improvement of immunological reactivity, ovarian hemodynamics in earlier terms in comparison with the traditional circuit of treatment. The received results demonstrate optimization of acute adnexitis current under influence of antihomotoxic medicines expressing in reduction of terms of disease and the period of restoration that excludes necessity additional measures for reabilitation.